Viral Population Changes during Murine Norovirus Propagation in RAW 264.7 Cells - Kitamoto, Takuya; Takai-Todaka, Reiko; Kato, Akiko; Kanamori, Kumiko; Takagi, Hirotaka; Yoshida, Kazuhiro; Katayama, Kazuhiko; Nakanishi, Akira (Frontiers in Microbiology, 2017)
Laboratory adaptation of viruses is an essential technique for basic virology research, including the generation of attenuated vaccine strains, although the principles of cell adaptation remain largely unknown. Deep sequencing of murine norovirus (MuNoV) S7 during serial passages in RAW264.7 cells showed that the frequencies of viral variants were altered more dynamically than previously reported. Serial passages of the virus following two different multiplicity of infections gave rise to distinct haplotypes, implying that multiple cell-adaptable sequences were present in the founder population. Nucleotide variants lost during passage were assembled into a viral genome representative of that prior to cell adaptation, which was unable to generate viral particles upon infection in cultured cells. In addition, presence of the reconstructed genome interfered with production of infectious particles from viruses that were fully adapted to in vitro culture. Although the key nucleotide changes dictating cell adaptation of MuNoV S7 viral infection are yet to be elucidated, our results revealed the elaborate interplay among selected sequences of viral variants better adapted to propagation in cell culture. Such knowledge will be instrumental in understanding the processes necessary for the laboratory adaptation of viruses, especially to those without relevant cell culture systems.